Образ города в прозаическом творчестве Нины Берберовой - Witczak, Patryk (Acta Neophilologica, 2020)
Nina Berberova – a representative of the first wave of Russian emigration – is known primarily as the author of the famous autobiography Kursiv moy. Berberova’s prose of the 1920s and 30s is the main topic of this article, in which the author refers to the tradition of Russian literature of the nineteenth and early twentieth century. The urban text created by Nina Berberova is considered in the paper as a hypertext; the author distinguishes the features of this textual formation and provides the exam-ples. This urban text is interpreted not as scattered fragments but as an integrated whole. The researcher tries to identify the interpreting code of a “Parisian text” of the first emigration wave closely associated with the myth which organizes this urban text.